Evaluation of the Effect of Different Doses of Gamma Radiation to Induce Variation in in vitro Raised Plants of Chrysanthemum (Plant Tissue Culture and Biotechnology, 2023)
Variation induction using gamma radiation in in vitro raised chrysanthemum is one of the most useful methods in floriculture. Different doses of gamma radiation have a negative effect on the in vitro shoot regeneration rate. Irradiation of in vitro micro shoots with highest dose 25Gy produced only 3.90% and 9.93% of BRAI Chry-1 and BARI Chry-2 micro shoots. But the lowest dose 5Gy could regenerate the highest percentage of shoots for both varieties. The LD50 obtained from the survival percentage of the irradiated in vitro raised shoots was found at 9.25 Gy for BARI Chry-1 and 11.19 for BARI Chry-2 variety. Successful mutation can be found around the LD50 doses of a specific genotype. During hardening of the M1V5 regenerants of BARI Chry-1 and BARI Chry-2 raised from 15Gy irradiated micro shoots showed highest variation regarding leaf structure, size of the internode and plant height. M1V5 regenerants developed from 10Gy of both varieties produced 20 to 50 percent variations. In future gamma radiation dose between 10-15Gy would be more effective to get variation in this flower.  Plant Tissue Cult. & Biotech. 33(2): 155-165, 2023 (December)